Climate impacts on soil susceptibility to erosion. - Dowdeswell-Downey, Emily (Cranfield University, 2020)
Soil erosion threatens soil sustainability and the provision of ecosystem services and is predicted to increase in the future with climate change. Soil erodibility, the susceptibility of soil to erosion, is often estimated as a constant variable but the best indicator of erodibility is aggregate stability, which is a dynamic soil property and has been observed to vary with changes in local climatic conditions. Aggregate stability is influenced by biological stabilisation and the soil microbial community are known to respond to changes in climatic conditions, yet whether aggregate dynamics can be explained by shifts in the soil microbial community has not been fully investigated. This thesis aims to investigate the influence of climatic conditions, in terms of soil temperature and moisture content, on aggregate stability, and thus soil erodibility, and whether these dynamics are explained by climate-induced changes in the soil microbial community. Environmental chambers and a rainfall simulator were used to examine the effects of climatic conditions and rainfall on aggregate stability and soil microbial properties as indicators of biological stabilisation in single-layer and multi-layered aggregate microcosms. The key findings show that temperature and moisture content significantly affected aggregate stability and the influence of soil temperature and moisture on soil microbial properties is soil texture dependent. Soil microbial properties were significant predictors of aggregate stability. Aggregate stability did not differ between climate scenarios in seasonal treatments but was significantly lower in seasonal treatments compared to constant seasons. Soil temperature and moisture significantly affected soil erodibility related to changes in aggregate stability and the soil microbial community. Rainfall significantly affected microbial properties in eroded soil and selectively mobilised a fungal-dominated component of the microbial community, influenced by preceding climatic treatments. The research highlights the further need to (i) recognise the role of climate-driven microbial shifts mediating aggregate stability mechanistically; and (ii) integrate knowledge on aggregate- scale mechanisms across larger spatial scales.
Keywords: Aggregate stability; soil erodibility; climatic conditions; temperature; moisture content; soil microbial community